2017
DOI: 10.5539/elt.v10n2p114
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Listening Strategies Used by Saudi EFL Medical Students

Abstract: The present study investigated the metacognitive listening strategies among Saudi EFL medical students. The participants were 104 males and females, randomly selected to fill in the Metacognitive Awareness Listening Questionnaire (MALQ), developed and validated Vandergrift Goh, Mareschal, and Tafaghodtari (2006). The results revealed that participants use problem-solving and direct attention strategies more frequently than other metacognitive listening strategies. On the other hand, mental translation and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 32 publications
2
24
1
Order By: Relevance
“…The result of this study is in line with previous studies, as cited by (Alhaisoni, 2017). Altuwairesh in (Altuwairesh, 2016) found that the subject used problemsolving strategies more than other types of metacognitive listening strategies.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The result of this study is in line with previous studies, as cited by (Alhaisoni, 2017). Altuwairesh in (Altuwairesh, 2016) found that the subject used problemsolving strategies more than other types of metacognitive listening strategies.…”
supporting
confidence: 92%
“…Listening in a foreign language is a complex but underestimated skill, as stated by Graham in 2003 cited by (Alhaisoni, 2017). On the otehr hand, since listening was believed on emphasizing and giving a boost for oral skills, many researchers are required to pay much attention to listening skill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the findings obtained as a result of the study, it can be said that sufficient metacognitive strategies are not used in teaching Turkish to Syrian children in order to improve their listening skills especially pre-listening and while listening whereas metacognition focuses on the listening process rather than how listening is concluded. Similarly, as a result of the study carried out by Alhaisoni (2017), it was also determined that evaluation, one of metacognitive listening strategies, in other words, the strategies used after listening were among the most frequently used strategies. Nevertheless, the findings obtained in some studies are different from the research result.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…reading and listening) (e.g. Alhaisoni, 2017;Sheorey & Mokhtari, 2001). It has been found that the learners' awareness and strategic knowledge about learning play a critical role in those activities (Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%